Medical Therapy to Facilitate Urinary Stone Passage - Muhammad Nasir Jamil, Muhammad Shahzad, Hamza Ashraf, Ehsan Ul Islam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary stones are now a worldwide problem due to a rise in occurrence over the past few decades. All racial and cultural groups have experienced this. Complex metabolic and environmental risk factors are both involved in the pathogenetic pathways of stone production. This disease affects roughly 12% of the world's population. Its recurrence rate is about 70% in men and 47% in women. Urinary stones have significantly increased in prevalence over the past 20 years, becoming a global disease. Aim: This review covers literature on the medical therapy of urolithiasis to facilitate urinary stone passage and their mechanism of action in the light of the new data on the diagnosis and different types of urinary tract stones. Method: A preliminary search of related articles was obtained from three online databases PubMed, Sci.hub and Google scholar whichwere used to conduct a systematic evaluation of the literature. Inclusion and exclusion criteria screened the initial search results, and 67 papers were chosen to be appropriate for this literature review following careful reading, analysis, and evaluation. Results: Different methods of medical therapy (phosphodiesterase-5 inhibitors, alpha blockers, calcium blockers, non-steroidal anti-inflammatory drugs and different types of surgical procedures (extracorporeal shock wave lithotripsy, percutaneous nephrolithotomy,ureteroscopy)were thoroughly reviewed but among all of them the expulsion rate to remove the urinary stone was found to be larger and faster in calcium channel blocker (CI 1.33-1.66) and alpha blockers(CI 1.152–7.45). Practical implications: Medical therapies facilitate the urinary-stone passagebut these therapies are not generally used. The choices for treating urinary stones are expanded by these techniques. Patients with big ureteral stones have had better results with medical expulsive therapy.Removing the urinary stones also decreases the chances of other diseases which happened as a result of urinary stone. There are many benefits of medical expulsive therapy which are diverse in nature andthis therapy minimizes the exposure to anesthesia and radiations. Conclusion: Different surgical procedures are used to remove the stones from the urinary passage. Despite of surgical procedures, medical expulsive therapy are more helpful. Alpha-blockers and calcium channel blockers are the main medical expulsive therapies for primary evacuation of urinary tract stones. Keywords: Urolithiasis, Urinary tract stones, Medical expulsive treatment.